Open versus laparoscopic cholecystectomy: a comparative study on patient parameters - Pateriya, Anurag; Agrawal, Mathura Prasad; Samar, Surendra Kumar (International Surgery Journal, 2021)
Background: The advent of laparoscopic surgeries have heralded a giant leap for minimally invasive surgeries and are now being used as a primary modality due to its various benefits. The use of laparoscopic surgeries has been limited only by patient related factors and in certain scenarios by lack of infrastructure availability. The present study aimed to provide a comparative review of the traditional and minimally invasive modalities. Methods: The study employed a comparative prospective randomized study model with 100 subjects divided in two groups based on modality employed. The operative and post-operative parameters were noted and presented. Results: The study displayed that the advent of post-operative complications as well as hospital stay duration was higher in traditional laparoscopic cholecystectomy cases. Conclusions: The study reiterated the long known fact that laparoscopic surgeries in gall stones is favorable from the patient perspective but is riddled with unavailability due to financial and infrastructure based concerns.